Does rapport-building boost the eyewitness eyeclosure effect in closed questioning? - Nash, Robert A. (Legal and criminological psychology, 2016)
Purpose. Several studies have documented that people's ability to correctly report details of witnessed events is enhanced when they merely close their eyes. Yet closing one's eyes in front of a stranger could sometimes create social discomfort, which other studies suggest can impair memory reports. This paper reports two experiments exploring the extent to which the memory benefits of eyeclosure are enhanced when efforts are taken to build interviewer/witness rapport, thus potentially reducing discomfort. Methods. In both studies participants observed filmed events and, afterwards, half underwent a basic rapport-building exercise with an interviewer. All participants then answered closed questions about specific details of the event, and half were instructed to close their eyes throughout this questioning. We recorded the proportion of questions answered correctly, incorrectly, or with ‘don't know’ responses. Results. Both eyeclosure and rapport-building separately enhanced correct responding. The data offer no evidence, though, that rapport-building moderated this eyeclosure benefit. This is despite the fact that rapport-building did appear to moderate the effect of eyeclosure on participants' self-reported comfort during the interviews. Conclusions. These studies give us initial cause for doubt over a hypothesized – but heretofore untested – social psychological constraint on the benefits of eyeclosure.